Immiscible CO2 Flooding Efficiency in Low-Permeability Reservoirs: An Experimental Investigation of Residual Oil Distribution - Yang, Ying; Zhou, Xiao-Feng; Sun, Le-Yin; Wang, An-Lun; Wei, Jian-guang; Li, Chen-Xi; Ke, Xiang (Frontiers in Earth Science, 2021)
Residual oil distribution plays a critical role in understanding of the CO2 flooding processes, but its quantitative research for reservoirs with different permeability levels rarely has been comprehensively conducted in the laboratory. This paper presents the results of an experimental study on the immiscible CO2 displacement efficiency in different permeability core samples and various oil distribution patterns prior to and after immiscible CO2 flooding. Experiments were conducted on four core samples extracted from the selected oil field with a permeability range from 0.210 to 66.077mD. Experimental results show that the immiscible CO2 can mobilize oil in ultra-low permeability environment, and achieve a reasonable displacement efficiency (40.98 %). The contribution of different oil distribution patterns to displacement efficiency varies in reservoirs with different permeabilities. With the increase of core permeability, the contribution of cluster and intergranular pore oil distribution patterns to displacement efficiency increases. However, oil displacement efficiency of corner and oil-film patterns trends to increase with lower permeability. Therefore, immiscible CO2 flooding is recommended for ultra-low permeability case, especially for reservoirs with larger amount of oil in corner and oil-film distribution patterns. Oil displacement efficiency calculated by immiscible CO2 flooding experiment results agrees reasonably well with that by core frozen slices observation. The results of this study has practical significance refer to effective development of low permeability reservoirs.